2006
DOI: 10.1128/mcb.01076-06
|View full text |Cite
|
Sign up to set email alerts
|

UV-B Radiation Induces Epithelial Tumors in Mice Lacking DNA Polymerase η and Mesenchymal Tumors in Mice Deficient for DNA Polymerase ι

Abstract: DNA polymerase(Pol ) is the product of the Polh gene, which is responsible for the group variant of xeroderma pigmentosum, a rare inherited recessive disease which is characterized by susceptibility to sunlightinduced skin cancer. We recently reported in a study of Polh mutant mice that Pol is involved in the somatic hypermutation of immunoglobulin genes, but the cancer predisposition of Polh ؊/؊ mice has not been examined until very recently. Another translesion synthesis polymerase, Pol , a Pol paralog encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
80
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 74 publications
6
80
2
Order By: Relevance
“…cells) exhibited significant sensitivity to UV-C irradiation (Ohkumo et al 2006). We also showed that expression of human Polg (hPolg) or mouse Polg (mPolg) rescued the UV sensitivity of XP-V cells (Yamada et al 2000).…”
Section: Expression Of Mouse Polg Fully Complemented the Uv Sensitivimentioning
confidence: 79%
See 1 more Smart Citation
“…cells) exhibited significant sensitivity to UV-C irradiation (Ohkumo et al 2006). We also showed that expression of human Polg (hPolg) or mouse Polg (mPolg) rescued the UV sensitivity of XP-V cells (Yamada et al 2000).…”
Section: Expression Of Mouse Polg Fully Complemented the Uv Sensitivimentioning
confidence: 79%
“…Cell culture, transfection and UV exposure Polh ) ⁄ ) and Polh ) ⁄ ) Poli ) ⁄ ) MEF cells were as described (Ohkumo et al 2006). The…”
Section: Methodsmentioning
confidence: 99%
“…It substantially distorts DNA and no single DNA polymerases in human cells can complete the translesion synthesis reaction alone. Both of the Y-family enzymes pol ι and pol η are involved in bypass and associated mutagenesis by UV radiation [26][27][28][29]. Pol ι is the only bypass DNA polymerase in human cells that correctly inserts an A opposite the first T of (6-4)PP; insertion opposite the second T of a (6-4)PP is errorprone [19].…”
Section: Mismatch Extension and Translesion Dna Synthesismentioning
confidence: 99%
“…Furthermore, the results of our biological and biochemical experiments strongly suggest that REV1 recruits pol to a stalled replication site through the interaction with the REV7 subunit of pol , and this recruitment mechanism plays an important role for pol to catalyze TLS. (34). Their genotypes were confirmed by genomic PCR (supplemental Fig.…”
mentioning
confidence: 99%